2019
DOI: 10.1080/15567036.2019.1576073
|View full text |Cite
|
Sign up to set email alerts
|

Primary recovery factor as a function of production rate: implications for conventional reservoirs with different drive mechanisms

Abstract: This study evaluates the dependency of production rate on the recovery of hydrocarbon from conventional reservoirs using MBAL simulator. The results indicated that the recoveries are sensitive to the production rate in almost all hydrocarbon reservoirs. It was also found that the recovery of volumetric gas drive reservoirs is not impacted by the production rate. In fact, any increase in the production rate improves gas recovery in weak and strong water drive reservoirs. Moreover, increasing the production rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Rates of depletion in the form of maximum field rate and average cumulative monthly production are relatively low. This is because rates of depletion are deliberately slowed and managed in line with predetermined maximum efficient rates of depletion to avoid lower ultimate recovery at the end of field life (Bruce, 1976; Posner, 1972; Raza et al, 2019; Sukubo & Obi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of depletion in the form of maximum field rate and average cumulative monthly production are relatively low. This is because rates of depletion are deliberately slowed and managed in line with predetermined maximum efficient rates of depletion to avoid lower ultimate recovery at the end of field life (Bruce, 1976; Posner, 1972; Raza et al, 2019; Sukubo & Obi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the supply and demand of petroleum have entered an unbalanced state with continuous oil exploitation and utilization. , Tertiary oil recovery technology (enhanced oil recovery) improves oil recovery significantly by regulating the interaction between oil and various injections, including the augment of reservoir pressure, the reduction of oil viscosity, and the modification of the reservoir state. , Polymer flooding technology is one of the chemical branches of tertiary oil recovery technology, which is a kind of valid approach to improve the sweep efficiency and recovery efficiency of reservoirs, and thus can increase the viscosity of the aqueous phase, adjust the oil/water mobility ratio, and stabilize the front of displacement. , …”
Section: Introductionmentioning
confidence: 99%
“…At low rates, the liberated gas segregates at the top of the reservoir and is produced rapidly, which as a result, depletes the reservoir energy and decreases oil recovery. Raza et al 28 presented a simulation study to evaluate the dependency of hydrocarbon recovery on production rate for gas and oil reservoirs of different drive mechanisms. The authors reported that oil recovery decreases with the increase of production rate for most drive mechanisms.…”
mentioning
confidence: 99%